ANALISIS PENERAPAN MANAJEMEN PERSEDIAAN PADA PT. CITRA NUSANTARA CATERING - Nuroh, Siti; Rifai, Ahmad; Sularno, Syahrian Owen; Ridwan, Wawan; Suherman, Ujang (CV. Anugerah Duta Perdana, 2024)
Supplies of raw materials is very important in the new company, so that it should be can be controlled. Control supplies the raw material that it should be supported by good cost efficiency. The purpose of this research is to determine the appropriate inventory management system for management of PT. Citra Nusantara Catering. This study uses Economic Order Quantity (EOQ) Methods. EOQ method uses some calculations in order to know the optimum stock for a company, the total costs, and the re-order point. The data used are primary data in the form of interview result. Results show that the company has yet effectively apply the right management supplies. Based on calculation using the formula costs overall, the EOQ method will allow the company to save more than the total cost compared to the company's inventory management system at this time. To produce the total cost of the inventory more efficiently through the quantity and frequenchy of the purchase of raw materials the company should implement an optimal EOQ method in doing inventory control